2022
DOI: 10.1556/1326.2021.00936
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tectorigenin, tectoridi, irigenin, and iridin in mouse blood after intravenous administration by UPLC-MS/MS

Abstract: Tectorigenin, tectoridin, irigenin, and iridin are the four most predominant compounds present in She Gan. She Gan has been used in traditional Chinese medicine because of its anti-inflammatory, hepatoprotective, anti-tumor, antioxidant, phytoestrogen-like properties. In this paper, a UPLC-MS/MS method was developed to measure the pharmacokinetics of tectorigenin, tectoridin, irigenin, iridin after intravenous administration in mice. A UPLC BEH C18 (50 mm × 2.1 mm, 1.7 μm particle size) chromatographic column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another study indicated that oral administration of tectorigenin (80 mg/kg) resulted in a C max of 1.46 ± 0.30 µg/mL and AUC (0-t) of 7.31 ± 1.20 µg/mL × h [176]. Additionally, sublingual intravenous administration of tectorigenin (5 mg/kg) resulted in an AUC (0-t) of 219 ± 94 ng/mL × h [177]. Pharmacokinetic studies of some TCMs, such as Shejin-liyan Granule, extracts of Belamcandae Rhizoma and rhizome of Iris tectorum, also described the pharmacokinetic characteristics of tectorigenin as the main component [178][179][180].…”
Section: Pharmacokinetics Of Tectorigeninmentioning
confidence: 99%
“…Another study indicated that oral administration of tectorigenin (80 mg/kg) resulted in a C max of 1.46 ± 0.30 µg/mL and AUC (0-t) of 7.31 ± 1.20 µg/mL × h [176]. Additionally, sublingual intravenous administration of tectorigenin (5 mg/kg) resulted in an AUC (0-t) of 219 ± 94 ng/mL × h [177]. Pharmacokinetic studies of some TCMs, such as Shejin-liyan Granule, extracts of Belamcandae Rhizoma and rhizome of Iris tectorum, also described the pharmacokinetic characteristics of tectorigenin as the main component [178][179][180].…”
Section: Pharmacokinetics Of Tectorigeninmentioning
confidence: 99%